Civilizational Pedagogical Systems - Intellectualization Of Educational Content As A Didactic Basis - X.A. Turakulov,; S. Buktakov, (International Scientific and Current Research Conferences, 2020)
This article considers the development of an organizational-structural model for the formation of civilized pedagogical systems. This article will be used by those who are concerned with improving future teacher training.